APPLICATION OF TEAM GAME TOURNAMENT (TGT) AS A COOPERATIVE LEARNING MODEL TO INCREASE STUDENTS’ LEARNING MOTIVATION OF CLASS X OTKP IN BUSINESS ECONOMICS LEARNING SUBJECTS AT SMK TELKOM PEKANBARU - Nabila Alfiyah Putri; Suarman Suarman; Hardisem Syabrus (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2023)
This paper is indicated by Business Economics students’ low learning motivation at class X OTKP of SMK Telkom Pekanbaru. This paper analyzes the differences in students’ learning motivation through the application of Team Game Tournament (TGT) as a cooperative learning model. This paper uses experimental research with the pre-experimental or quasi-experimental with the One-group pretest and posttest research design. The research was conducted at Telkom Vocational School Pekanbaru for students at class X of Office Administration who took Business Economics as an Experiment class. Data were collected through questionnaires and observation sheets. Data were analyzed using descriptive statistics through the N-gain test and paired sample t-test. The results indicate that the average student’s learning motivation was higher than the average student’s learning motivation before the application of the Team Game Tournament (TGT) learning model. It is proven from the results of the N-Gain test and Paired Sample T-Test that there are significant differences in students’ learning motivation after and before applying the model. Thus, one of the methods that can be applied by the teacher to increase students’ learning motivation is to apply the Team Game Tournament (TGT) cooperative learning model.